Genetic evolution of classical swine fever virus under immune environments conditioned by genotype 1‐based modified live virus vaccine. Issue 3 (10th January 2018) - Yoo, S. J.; Kwon, T.; Kang, K.; Kim, H.; Kang, S. C.; Richt, J. A.; Lyoo, Y. S.
Summary: Modified live vaccines (MLVs) based on genotype 1 strains, particularly C‐strain, have been used to prevent and control classical swine fever virus (CSFV) worldwide. Nevertheless, a shift in the predominant CSFV strains circulating in the field from genotype 1 or 3 to genotype 2 is seen. Genotype 2 is genetically distant from the vaccine strains and was recently reported during outbreaks after vaccine failure; this has raised concerns that vaccination has influenced viral evolution. In Korea in 2016, there was an unexpected CSF outbreak in a MLV‐vaccinated commercial pig herd. The causative CSFV strain was genetically distinct from previously isolated Korean strains but similar to recent Chinese strains exhibiting enhanced capacity to escape neutralization; this suggests the need for global cooperative research on the evolution of CSFV. We analysed global E2 sequences, using bioinformatics tools, revealing the evolutionary pathways of CSFV. Classical swine fever virus genotypes 1 and 2 experienced different degrees and patterns of evolutionary growth. Whereas genotype 1 stayed relatively conserved over time, the genetic diversity of genotype 2 has progressively expanded, with few fluctuations. It was determined that genotype 2 evolved under lower immune pressures and at a higher evolutionary rate than genotype 1. Further, several selected codons, under diversifying selection in genotype 1 but under purifying selection in genotype 2, correspond to antigenic determinants, which could lead to evasion of vaccine‐induced immunity. Our findings provide evidence that evolutionary changes in CSFV are the result of the disproportionate usage of the CSF MLVs in endemic areas; this underscores the need to develop mitigation strategies to minimize the substantial risk associated with the emergence of vaccine‐escaping mutants.